EFEKTIVITAS BERBAGAI KONSENTRASI EKSTRAK DAUN MENGKUDU (Morinda citrifolia) UNTUK MENEKAN PERTUMBUHAN Colletotrichum capsici SECARA IN VITRO - Risda Adinda Wongkar; Rosmini Rosmini; Irwan Lakani (Fakultas Pertanian, Universitas Tadulako, 2022)
Cayenne pepper (Capsicum frutescens L.) is a popular chili spice widely used in Indonesian cuisine, and its demand has been increasing in the market. However, humid condition and pest attacks are common obstacles that can lead to a production decrease in chili plantation. This study aimed to determine the appropriate concentration of Morinda citrifolia (M. citrifolia) leaf extract to suppress the growth of Colletotrichum capsici, a fungus that causes anthracnose disease in chili plants. The experiment was conducted in vitro using a completely randomized design (CRD) of one factor with five treatments, and each treatment was repeated four times. The treatments included PDA media with no extract (K0), PDA media with 0.4 ml extract (K1), PDA media with 0.6 ml extract (K2), PDA media with 0.8 ml extract (K3), PDA media with 1 ml extract (K4). The study found that the addition of M. citrifolia leaf extract to the PDA medium produce significantly different effects on the growth of C. capsici colonies. The results of the data analysing using the 5% Tukey HSD test showed that the concentration of 1 ml extract added to the PDA media in the K4 treatment was the most effective in suppressing the growth of C. capsici colonies on the seventh day, with a diameter of 2.40 cm. In addition to suppressing the growth of C. capsica colonies, the extract at a concentration of 1 ml could also inhibit the growth of C. capsica with an inhibitory power of 66.84% on the fifth day.